Evaluation of BB84 Distribution Quantum Key protocol performance - معلا, بشرى (Latakia University Journal -Engineering Sciences Series, 2025)
Information and communication technology has developed to an integral part of our lives, and has deeply entered into the folds of culture, economy, defense, society, finance, and regional and international organizations. This development was accompanied by the emergence of major security risks and challenges that threaten society, so there was an urgent need to achieve a good level of security. Quantum encryption emerged as a qualitative leap to protect data and information by taking advantage of the scientific renaissance in the world of quantum physics. Quantum encryption is a high-tech method for securing digital communications by taking advantage of quantum principles, which are the cornerstone of this encryption, as it relies on taking advantage of the unique properties of quantum particles, which ensures unbreakable encryption. One of the most famous quantum encryption algorithms is the BB84 algorithm. Therefore, this research aims, on the one hand, to provide a detailed explanation of quantum encryption, and on the other hand, to demonstrate the effectiveness of this algorithm in generating a secure random key to be used in symmetric encryption applications, where distributing the key to users is one of the biggest problems that threaten its safe use. The research also seeks to clarify the effectiveness of this algorithm in detecting any eavesdropper trying to obtain the key.